2020
DOI: 10.1002/eqe.3261
|View full text |Cite
|
Sign up to set email alerts
|

A vector‐valued intensity measure for near‐fault ground motions

Abstract: Near-fault ground motions containing high energy and large amplitude velocity pulses may cause severe damage to structures. The most widely used intensity measure (IM) is the elastic spectral acceleration at the fundamental period of the structure (Sa(T 1 )); however, Sa(T 1 ) is not a sufficient IM with respect to the effects of the pulse-like ground motions on structural response. For nearfault ground motions, including pulse-like and non-pulse-like time histories, we propose a vector-valued IM consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 39 publications
(74 reference statements)
1
23
0
2
Order By: Relevance
“…It can be seen that the maximum IP occurs at around 10 seconds, which corresponds to the steepest slope of the CSV. The previous findings showed that the IP has a significant influence on the structural response after eliminating the effects of spectral shape and amplitude of the ground motions [2][3][4].…”
Section: Instantaneous Powermentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the maximum IP occurs at around 10 seconds, which corresponds to the steepest slope of the CSV. The previous findings showed that the IP has a significant influence on the structural response after eliminating the effects of spectral shape and amplitude of the ground motions [2][3][4].…”
Section: Instantaneous Powermentioning
confidence: 99%
“…For instance, characterization of the near-fault ground motions including velocity pulses requires the determination of the probability of the presence of a pulse, the period of the pulse, as well as the amplitude of the pulse. The recent study showed that the vector IM consisting of Sa(T 1 ) and Instantaneous Power (IP(T 1 )) sufficiently and efficiently captures the destructive impact of the near-fault ground motions on structural response [2]. In order to capture the damaging characteristics of these motions, it is necessary to consider the combined effects of relevant IMs, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This is analogous to the concept of vector-valued IMs (Baker, 2007). Several researchers have applied this sophistication to develop enhanced IMs (IM*), which consist in a vector of IVs providing more efficient estimates of EDPs (Modica and Stafford, 2014;Yakhchalian et al, 2015;Bojórquez et al 2015;Ge and Zhou, 2018;Zengin and Abrahamson, 2020;Yakhchalian et al, 2021). The amount of efficiency that can be gained by an IM depends on the correlation value between the residuals of the IM-EDP cloud and SP.…”
Section: Sufficiencymentioning
confidence: 99%
“…To study the response of structure to near-fault pulses with different periods, artificial ground motions have been used. For this purpose, regarding the fact that directivity and fling pulses have a relatively deterministic nature, some researchers tried to present synthetic models for these pulsetype motions (for example, [27][28][29][30][31][32][33]). In this study, the model proposed by Mavroeidis and Papageorgiou [34] has been used to mathematically express the directivity pulse.…”
Section: Mathematical Near-fault Pulse Modelsmentioning
confidence: 99%